Twelve Years an Editor – Almost. Nordic-Mediterranean Perspectives on Iceland’s International Image - Giorgio Baruchello (The University of Akureyri, 2016)
Established in 2005, the scholarly venue entitled Nordicum-Mediterraneum: Icelandic E-Journal of Nordic and Mediterranean Studies has been published regularly by the University of Akureyri since 2006. Over the years, its editor and editorial collaborators have received, read, reviewed and released a number of contributions by foreign scholars, in particular Italian ones, dealing with Iceland under a broad variety of scientific and scholarly perspectives. Upon the basis of the published contributions, the conference’s discussion can be enriched by an eminently local, quintessentially academic, yet qualitatively rich account of Iceland’s image among foreign academic circles, especially Italian ones.